A comparative analysis of financial literacy levels and initiatives among students in five European countries. (18th June 2022) - Cannistrà, Marta; Agasisti, Tommaso; Amagir, Aisa; Poder, Kaire; Holz, Oliver; Vartiak, Lukas; De Witte, Kristof
Given the expected advantages for individuals and societies, financial literacy is high on the policy agenda in many countries. This paper reports the results from a unique survey conducted on a sample of 13–16-year-old students in five European countries, aimed at measuring and comparing their level of financial literacy skills. The results indicate significant differences in the level of financial literacy across countries that are interpreted in the light of the differences in the countries' educational policies and experiences with financial education. The findings suggest that supra-national coordinated action is needed to guarantee better financial knowledge and safeguard economic stability in future crises. JEL-classification : I21; G53; O57; O16.